REGIONAL FEATURES OF ECOLOGICAL GEOCHEMICAL CONDITION OF SURFACE WATER BODIES IN TAIGA ZONE OF WESTERN SIBERIA - Mikhail L. Markov; Tatyana M. Potapova; Olga V.Zadonskaya (Izvestiya Tomskogo Politekhnicheskogo Universiteta Inziniring Georesursov, 2020)
Relevance.Quantitative assessment of ecological and geochemical state of surface waters and their formation factors is one of the most important stages of water resources management which determines the effectiveness of measures for integrated use and protection of waters. The aim of the research isthequantitative assessment of regional features of the current ecological and geochemical state of surface water bodies in the taiga zone of Western Siberia. Methods:methods ofwater chemical composition researches (titrimetric, turbidimetric, photometric, ion chromatography, inversion-voltamperometric, atomic absorption, mass spectrometric with inductively coupled plasma); statistical methods. Results and conclusions.The authors have considered regional features of ecological and geochemical state of surface water bodies in taiga zone of Western Siberia by the results of analysis of the materials of long-term hydrochemical observations of Roshydromet and other organizations.It is shown that chemical composition of surface waters in the region is largely determined by the natural wetland processes, resulting in an excess of fishery and drinking quality standards for the pH value, the content of NH4+, Fe, Al, Mn, phenols, substances identified as «petroleum products», as well as fishery standards – for the content of NO2–, phosphates, Cu, Zn and drinking –the value of bichromate and permanganate oxidability. It is established that anthropogenic influence is reliably detected by increasing the chloride ion content (within the maximum permissible concentrations, but 2–3 times higher than the background values). The authors developed the recommendations on hydrochemicalmonitoring.On the basis of regional background concentrations of pollutants and water dischargeon the regime stations of Siberian rivers the degree of dilution of wastewater dropped into the rivers of strongly swampy watershedscan be determined. These calculations should be the basis for the approved standards of permissible impacts on the riversof the taiga ...